Factors Affecting Dividend Policy In Companies In The Era of Covid-19 Pandemic - Ariani, Marieta; Wijayanto, Rakendro; Raharjo, Tyas Pambudi; Hasnawati, Hasnawati; Oktaviani, Oktaviani (Green Publisher Indonesia, 2023)
This study aims to examine the effect of free cash flow, profitability, collateralizable asset and debt policy on dividend policy. The method of data analysis in this study uses the method of multiple regression analysis on Eviews program assistance and data collection method using purposive sampling. The data used are secondary data obtained from 81 data financial statements of sector property, real estate and building construction companies listed on the Indonesia Stock Exchange in 2019-2021. The results of this study indicate that the free cash flow and collateralizable assets variable has a positive influence on dividend policy, while profitability and debt policy variable has no postitive effect on dividend policy